AB0439 YTTRIUM-90 SYNOVIORTHESIS. OUR EXPERIENCE FOR 25 YEARS. (June 2019) - Lavilla, Patricia; Retuerto-Guerrero, M.; Melchor, Sheila; Martos, Álvaro García; Vega, Diana; Alonso, Pilar; Dapica, Pilar F.
Abstract : Background: Radioactive synoviorthesis (RS) is the intra-articular injection of a colloidal suspension of particles marked with a radioisotope that selectively irradiates the synovial membrane, respecting bone and cartilage. The radiocolloid is phagocytosed by type 2 synoviocytes of the synovial membrane, causing fibrosis and decreased production of synovial fluid. Intra-articular puncture is ensured by obtaining synovial fluid and then the radiopharmaceutical is instilled followed by 1ml of triamcinolone acetoide (40mg). After the procedure a graphic gamma image is made to assess the adequate distribution of the radionuclide in the joint cavity. With a half-life of 2.5 days, the drug will continue to emit radiation for weeks, with symptomatic improvement which is observed from the second week. The main indication of this technique is refractory chronic synovitis to local and/or systemic treatment. Objectives: To describe the clinical-demographic characteristics of patients treated with SR in our hospital, and to asses the efficacy and safety of this technique. Methods: Retrospective observational study that analyze the radiosynoviorthesis practiced in the Nuclear Medicine service of the Doce de Octubre Hospital between January 1994 and December 2018 is analyzed. A total of 113 techniques were analyzed in 89 patients from our center and other hospitals without Nuclear Medicine service, and data of 72 patients could be obtained from their clinical history. The efficacy of the technique was defined as total or partial, considering objective data (swelling and joint function) and subjective data (patient evaluation). Results: 95 articular instillations were included in 72 patients, 46% women and 54% men; with an average age of 51.4 ± 15 |21-82| years, the knee articulations were injected with Yttrium-90 (5 millicuries). The patients had knee effusions lasting for an average of 18 months (IR 10-60). The temporal distribution was very heterogeneous, decreasing over the years (1994-1998: 23%, 1999-2003: 32%, 2004-2008: 20%, 2009-2013: 16%, 2014-2018: 9%). 93% of RS were indicated by the rheumatology service and 7% by traumatology. In the classification by pathologies, 72.2% had systemic rheumatological disease. The most frequent causes of indication were rheumatoid arthritis (25%), psoriatic arthropathy (24%), spondyloarthropathy (17%) and pigmented villonodular synovitis (11%). Less frequent were juvenile idiopathic arthritis (5%), arthrosis (4%), microcrystalline arthritis (5%) and non-specific chronic synovitis (9%). 79% had been previously infiltrated with steroid, with an average of 2.8 ± 1.8 |1-10| injections/knee. The 79% had maintained treatment with NSAID, the 42% with systemic steroid, the 55% with DMARDs and the 14% with biological therapy; appearing the therapeutic effect in the first 8 weeks in the 80% of the patients. 13 patients needed a reinstill with an average between radiosynoviorthesis of 25 ± 21 |6-80| months. Side effects were scarce (2.8%) and local in nature; 8.3% required a knee prosthesis. Conclusion: RS has demonstrated acceptable efficacy and safety in cases of refractory synovitis of both mechanical and inflammatory etiology. Despite this, it is a procedure little used nowadays. Disclosure of Interests: None declared